2003
DOI: 10.1007/s00221-003-1470-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of return and the human frontal eye fields

Abstract: Inhibition of return (IOR) is a bias against reorienting attention to a previously cued location. In this study, using single-pulse transcranial magnetic stimulation (TMS), we show that the human frontal eye fields (FEF) play a crucial role in the generation of IOR. When TMS was applied over the right FEF at a time interval after a visual cue but shortly before the target, IOR was modulated in the hemifield ipsilateral to the TMS such that responses to a previously cued target were no longer slower than respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 55 publications
10
54
0
Order By: Relevance
“…This reprogramming may be necessary at invalidly cued locations after an endogenous cue, because a link has been established with the cued location and at cued locations at long SOAs after an exogenous cue, because IOR may have prevented or weakened the formation of a link to the exogenously cued location. This idea is consistent with previously noted TMS work in the FEF (Ro et al, 2003). Conversely, regions in the TPJ and VFC contain multimodal sensory responses that are spatially nonselective (Corbetta et al, 2000;Downar et al, 2000;Macaluso et al, 2002) and are not modulated by response factors (Braver et al, 2001;Astafiev et al, 2004).…”
Section: Ventral and Dorsal Frontoparietal Regions In Stimulus-drivensupporting
confidence: 91%
See 1 more Smart Citation
“…This reprogramming may be necessary at invalidly cued locations after an endogenous cue, because a link has been established with the cued location and at cued locations at long SOAs after an exogenous cue, because IOR may have prevented or weakened the formation of a link to the exogenously cued location. This idea is consistent with previously noted TMS work in the FEF (Ro et al, 2003). Conversely, regions in the TPJ and VFC contain multimodal sensory responses that are spatially nonselective (Corbetta et al, 2000;Downar et al, 2000;Macaluso et al, 2002) and are not modulated by response factors (Braver et al, 2001;Astafiev et al, 2004).…”
Section: Ventral and Dorsal Frontoparietal Regions In Stimulus-drivensupporting
confidence: 91%
“…IOR is an inhibitory mechanism that prevents the reexploration of a previously visually cued location. A recent transcranial magnetic stimulation (TMS) study showed that stimulation over the human FEF, but not IPS, disrupts the formation of IOR in the ipsilateral visual field (Ro et al, 2003).…”
Section: Exogenous Orienting To Color Singletonsmentioning
confidence: 99%
“…Note that the neural locus of IOR phenomena is most likely not limited to only the SC (see, e.g., Dorris et al, 2002;Ro, Farnè, & Chang, 2003). One common example is that IOR can inhibit locations in space-fixed coordinates rather than retinotopic coordinates-a feature not congruent with the retinotopic maps observed in the SC.…”
Section: Discussionmentioning
confidence: 99%
“…Ignashchenkova et al 2004). Temporarily disrupting neuronal activity in one such interface between attention and eye movements, the frontal eye Weld (FEF), eliminated IOR with manual responses (Ro et al 2003).…”
Section: Introductionmentioning
confidence: 99%